Re-evaluation of Streptococcus pneumoniae carriage in Portuguese elderly by qPCR increases carriage estimates and unveils an expanded pool of serotypes - Almeida, Sónia T. (2020)
Streptococcus pneumoniae (pneumococcus) is a leading cause of infections worldwide. Disease is preceded by asymptomatic colonization of the upper respiratory tract. Classical culture-based methods (CCBM) suggest that colonization in the elderly is <5%. Recently, use of qPCR has challenged these observations. We estimated pneumococcal carriage prevalence and serotypes among Portuguese elderly using qPCR and compared results with those obtained by CCBM. Nasopharyngeal and oropharyngeal paired samples (599 each) of individuals over 60 years living in nursing (n = 299) or family (n = 300) homes were screened for the presence of pneumococci by qPCR targeting lytA and piaB. Positive samples were molecular serotyped. Use of qPCR improved detection of pneumococci in oropharyngeal samples compared to CCBM: from 0.7% to 10.4% (p < 0.001) in the nursing home collection, and from 0.3% to 5.0% (p < 0.001) in the family home collection. No significant differences were observed between both methods in nasopharyngeal samples (5.4% vs. 5.4% in the nursing homes; and 4.3% vs. 4.7% in the family homes). Twenty-one serotypes/serogroups were detected by qPCR compared to 14 by CCBM. In conclusion, use of qPCR suggests that pneumococcal carriage in Portuguese elderly is approximately 10%, and unveiled a large pool of serotypes. These results are important to understand progression to disease and impact of pneumococcal vaccines in the elderly.